Neighborhood Characteristics and Frailty: A Scoping Review. (5th July 2019) - Fritz, Heather; Cutchin, Malcolm P; Gharib, Jamil; Haryadi, Neehar; Patel, Meet; Patel, Nandit
Abstract: Background and Objectives: Frailty is highly prevalent in later life and associated with early mortality and adverse health outcomes. The neighborhood has been identified as an important contributor to individual health, and neighborhood characteristics may contribute to frailty development. A scoping review was conducted of the peer-reviewed literature to better understand how physical and social neighborhood characteristics contribute to frailty. Research Design and Methods: Following an established scoping review methodology, we searched four peer-reviewed databases for relevant studies published from January 1, 2008, to December 31, 2018. Data extracted from studies included study characteristics, operationalization of neighborhood, the conceptual model of the neighborhood–frailty relationship, operationalization of frailty, and study findings for associations among neighborhood variables and frailty indicators. Results: A total of 522 articles were identified and 13 articles were included in the final data charting. Existing studies suggest that neighborhood characteristics are associated with frailty in later life. Few studies articulated a conceptual model identifying exact mechanisms through which neighborhood factors affected frailty. Studies designs were mostly cross-sectional. Longitudinal studies did not measure neighborhood characteristics over time. Studies varied considerably in how they operationalized the neighborhood. Frailty was most commonly assessed using a 5-point phenotype or a frailty index approach. Discussion and Implications: Findings indicate that research on the relationship between neighborhood characteristics and frailty is an emerging area of inquiry. Additional studies are needed to more definitely explicate mechanisms through which neighborhoods contribute to, or protect older adults from, frailty.